Doors Half-Open in Bluebeard’s Castle: George Steiner and His Heretical Essays in Modern Times - Kleprlík, Michal (My University, 2021)
George Steiner was a French-American polymath and polyglot. Along with Umberto Eco, Steiner has been ranked among the very last European metaphysicians as well as a leading cultural critic of the 20th century. Although an erudite scholar writing extensively in four languages about the most pressing issues of late modernity, Steiner has never been very popular among the general public. While his original essays won critical acclaim, by intellectuals he has also been rebuked for his ill-judged, doom-laden and reactionary elitist visions. The paper deals with Steiner’s most thought-provoking, “heretical” texts on the nature of modern barbarism and the basic inhumanity at the heart of the humanities. The aim is to suggest possible reasons for Steiner’s “persona non grata” status.
Pootevírání komnat na Modrovousově hradě: George Steiner a jeho kacířské eseje
Keywords: George Steiner; Holocaust; humanities; culture; post-culture; literacy; heresy; Steiner; holokaust; humanitní studia; kultura; postkultura; gramotnost; kacířství